Exploring the potential of low-dimensional materials from cigarette butts for energy applications: A comprehensive review - Ye Chen; Shilong Li; Congxin Xia; Miao Tian; Yaxin Guo; Xupo Liu; Mingjin Cui; Shixue Dou; Hanleem Lee; Vadivel Subramaniam; Krishnamoorthy Ramachandran; Xinghui Liu (Advanced Powder Materials)
Carbon-based low-dimensional materials (CLDM) with elemental carbon as the main component have unique physical and chemical properties, and become the focus of research in many fields including energy, environmental protection, and information technology. Notably, cellulose acetate, the main component of cigarette butts (CBs), is a one-dimensional precursor with a large specific surface area and aspect ratio. Still, their usefulness as building fillers has often been underestimated before. This review summarizes recent advances in CBs recycling and provides suggested guidelines for its use as a CLDM material in renewable energy. Specifically, we first describe the harmful effects of CBs as pollutants in our lives to emphasize the importance of proper recycling. We then summarize previous methods of recycling CBs waste, including clay bricks, asphalt concrete pavement, gypsum, acoustic materials, chemisorption, vector control, and corrosion control. The potential applications of CBs include triboelectric nanogenerator applications, flexible batteries, enhanced metal-organic framework material energy storage devices, and carbon-based hydrogen storage. Finally, the advantages of utilizing CBs-derived CLDM materials over conventional solutions in the energy field are discussed. This review will provide new avenues for solving the intractable problem of CBs and reducing the manufacturing costs of renewable materials.